Prevalence and Patterns of Drug Use Among People in Al-Najaf Governorate, Iraq - Hakim, Hasanein I.; Abdul-Hassan, Layla Saleh; Alkhudhairy, Miaad K. (Medical Science Journal for Advance Research, 2024)
Background: After a series of instability Iraq confronted in the past decades, the drug abuse issue has grown and is now a complex national concern where the rise in drug transshipment through the country and neighbor countries accompanies noticeable increased consumption of drugs especially those associated with transnational criminal networks such as amphetamines. This is a descriptive cross-sectional epidemiological study conducted in Al-Najaf governorate from January to March 2024, qualitative data based on the correction institutions of the Ministry of the Interior using a non-probability sample since lack of precise sample frame or data about the real prevalence or rate of the problem. The study recruited 288 drug users all between 20-64 years, 31(10.8%) were females and 257(89.2%) were males (49%). 237 (82%) of the drug users of young adults between 20 to 40 years old. The objective was to investigate personal history and examine the extent and patterns of the abuse of drugs, using a structured questionnaire designed and modified after reviewing relevant studies. The study found that the majority of the participants smoked nicotine throughout their lifetime as 60.8% smoked hookah, 15% smoked e-cigarettes and 86% smoked cigarettes with about 75% current heavy smokers, 51% of participants used alcohol as lifetime prevalence with more than 32% used it weekly. A large percentage: 88% abused more than one type of illicit drug with amphetamine stimulants (methamphetamine and fenethylline) as the most commonly abused illicit drugs among the majority of the participants. The lifetime prevalence of prescription drug use was 86%. 60% used more than one method of administration, while 8% used drugs by injection. The study concluded that a large percentage of the study participants were polydrug abusers with extensive patterns of use which revealed the complex status of which stresses a holistic approach to managing the problem. Conclusion: The study concluded that a large percentage of the study participants were polydrug abusers with extensive patterns of use which revealed the complex status of which stresses a holistic approach to manage the problem.